Alternative Oxidase: A Potential Target for Controlling Aflatoxin Contamination and Propagation of Aspergillus flavus - Tian, Fei; Lee, Sang Yoo; Woo, So Young; Chun, Hyang Sook (Frontiers in Microbiology, 2020)
Aflatoxins are among the most hazardous natural cereal contaminants. These mycotoxins are produced by Aspergillus spp. as polyketide secondary metabolites. Aflatoxigenic fungi including A. flavus express the alternative oxidase (AOX), which introduces a branch in the cytochrome-based electron transfer chain by coupling ubiquinol oxidation directly with the reduction of O2 to H2O. AOX is closely associated with fungal pathogenesis, morphogenesis, stress signaling, and drug resistance and, as recently reported, affects the production of mycotoxins such as sterigmatocystin, the penultimate intermediate in aflatoxin B1 biosynthesis. Thus, AOX might be considered a target for controlling the propagation of and aflatoxin contamination by A. flavus. Hence, this review summarizes the current understanding of fungal AOX and the alternative respiration pathway and the development and potential applications of AOX inhibitors. This review indicates that AOX inhibitors, either alone or in combination with current antifungal agents, are potentially applicable for developing novel, effective antifungal strategies. However, considering the conservation of AOX in fungal and plant cells, a deeper understanding of fungal alternative respiration and fungal AOX structure is needed, along with effective fungal-specific AOX inhibitors.